AN ANALYSIS ON THE TRANSLATION OF REPETITIVE INDONESIAN ADJECTIVE INTO ENGLISH - Arsiwela, Arsiwela (Universitas Gunadarma, 2019)
The function of translation is to convey meaning or message from source language text into target language text. However, in translating, the translator will face some problems, for example is the translation of repetitive Indonesian adjectives. This study investigates how repetitive Indonesian adjectives are translated into English. Indonesian has repetitive adjectives such as tinggi-tinggi, cantik-cantik, and jauh-jauh and the English translation of the repetition is not tall-tall, beautiful-beautiful, and far-far respectively. The method applied in this study is qualitative descriptive method. The data will be categorized and classified and then analyzed in accordance with the principle, translation strategies, and relevant theories. The result of the study shows that literal translation strategy and transposition strategy are the most frequent strategy used by the translator. Some of them are translated in the different form grammatically but the meaning of the message in source language is well maintained into the target language. The principle of translation employed by the translator to translate Indonesian repetitive adjective is meaning.